THE DETERMINATION OF INCENTIVE GIVING OF LAND AND BUILDING TAX (PBB) ON VEGETATED LAND IN URBAN AREA - DWIATMOKO (NIM 25106030), SUMANTRI
The recent urban development has increased temperature, air pollution and water pollution, reduced soil ability of water absorption, and caused another environment demolition. World temperature increased amount to 0,18oC among last 25 years as the effect of green house concentration increasing, it’s known as global warming phenomenon. Green house effect affected a lot of earth heat radiation that trapped in atmosphere which caused world temperature increasing. It affected global climate change. Vegetation as a part of ecosystem has implication and plays the role of supporting life system. The vegetation great functions are water supplier, carbon absorber, oxygen supplier, and global climate regulator. PBB is a direct tax on land, so it can be used in environment conservation by incentive giving on vegetated land in urban area. The modeling of PBB incentive giving using 6 category of discriminator with the independent variables are vegetated area (LV) and Building Coverage Ratio Appropriate Level (TKKDB). Vegetated area are obtained by intersection of vegetation map (that derived from digitized Quickbird image) and integrated PBB map. The TKKDB of each parcel was obtained from function of Building Coverage Ratio (KDB) and KDB existing. KDB design was obtained from spread KDB map, while existing KDB was obtained from building area that divided by parcel area. The formula determination of incentive giving of land and building tax could be done by ZScore1 = -0,657 + (0,467LV) + (0,010TKKDB) and ZScore2 = -0,601+ (-0,075LV) + (0,035TKKDB). The reducing of land and building tax revenue as the consequence of land and building tax incentive reward on vegetated land in Terban sub district amount to Rp3.812.208,- or 2,34% from Rp162.781.853,-. It could support civilization to play the role of environment management by plant vegetation on their parcel.